Low and decreasing vaccine effectiveness against influenza A(H3) in 2011/12 among vaccination target groups in Europe: results from the I-MOVE multicentre case-control study - Kissling, E. (2014)
Within the Influenza Monitoring Vaccine Effectiveness in Europe (I-MOVE) project we conducted a multicentre case–control study in eight European Union (EU) Member States to estimate the 2011/12 influenza vaccine effectiveness against medically attended influenza-like illness (ILI) laboratory-confirmed as influenza A(H3) among the vaccination target groups. Practitioners systematically selected ILI / acute respiratory infection patients to swab within seven days of symptom onset. We restricted the study population to those meeting the EU ILI case definition and compared influenza A(H3) positive to influenza laboratory-negative patients. We used logistic regression with study site as fixed effect and calculated adjusted influenza vaccine effectiveness (IVE), controlling for potential confounders (age group, sex, month of symptom onset, chronic diseases and related hospitalisations, number of practitioner visits in the previous year). Adjusted IVE was 25% (95% confidence intervals (CI): -6 to 47) among all ages (n=1,014), 63% (95% CI: 26 to 82) in adults aged between 15 and 59 years and 15% (95% CI: -33 to 46) among those aged 60 years and above. Adjusted IVE was 38% (95%CI: -8 to 65) in the early influenza season (up to week 6 of 2012) and -1% (95% CI: -60 to 37) in the late phase. The results suggested a low adjusted IVE in 2011/12. The lower IVE in the late season could be due to virus changes through the season or waning immunity. Virological surveillance should be enhanced to quantify change over time and understand its relation with duration of immunological protection. Seasonal influenza vaccines should be improved to achieve acceptable levels of protection.